Efficacy of partial embolization of splenic artery in patients after hemorrhage of portal genesis - V. V. Petrushenko; D. І. Grebeniuk (Клінічна хірургія)
Objective. To assess the efficacy of partial embolization of splenic artery in patients after hemorrhage of portal genesis.